Storyteller’s Role In "Sehat Ceria di masa Pandemi" Comics To Students Of Gudang 1 Sumedang Public Elementary School - Dida, Susanne; Lusiana, Elnovani; Dewi, Retasari; Gobel, Sry Ade Muhtya; Muslimin, Fauzy Akmal (Jurnal Komunikasi, 2023)
Corona Virus Disease 2019 (Covid-19), one of the most dangerous viruses spread to cause outbreaks in almost all countries, including Indonesia. Based on the latest data on October 19, 2022, the number of positive Covid-19 patients in Indonesia is 6,450,248. The Covid-19 pandemic has significantly impacted daily life because almost all countries in the world are working hard to find preventive measures so that the spread of Covid-19 does not continue to increase. For example, large-scale social restrictions, physical distancing rules, and carrying out regional quarantine with two events, full and limited. Apart from that, in the field of education, the government issued a distance education regulation Circular Letter Number 4 of 2020 Concerning Implementation of Education Policies in an Emergency Period of the Spread of Corona Virus Disease (Covid-19). The method used in this study is qualitative method with a case study approach. This study interpreted the case of the storyteller's unique role, which was a strategy to understand the essence of the story in comics to an audience of elementary school children. The results found that the storyteller was the main factor in persuading children. In persuading children of elementary school, a storyteller should have a strategy in storytelling and pay the most attention to children's concentration time.